The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2177-6709.21.2.073-080.oar
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant evaluation of osseointegrated implants subjected to orthodontic forces: results after three years of functional loading

Abstract: Objective: The objective of this study was to clinically and radiographically assess the peri-implant conditions of implants used as orthodontic anchorage. Methods: Two groups were studied: 1) a test group in which osseointegrated implants were used as orthodontic anchorage, with the application of 200-cN force; and 2) a control group in which implants were not subjected to orthodontic force, but supported a screw-retained prosthesis. Clinical evaluations were performed three, six and nine months after prosthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…This case series showed the conservation of the implant osseointegration despite bone- implant complex movement. Osseointegrated implants used as orthodontic anchorage showed a force resistance, without peri-implant bone changes in animal models or human use [ 31 , 32 ]. Melsen & Lang, in an animal study, have applied orthodontic forces of 100, 200, and 300 g in three different osseointegrated implant groups.…”
Section: Discussionmentioning
confidence: 99%
“…This case series showed the conservation of the implant osseointegration despite bone- implant complex movement. Osseointegrated implants used as orthodontic anchorage showed a force resistance, without peri-implant bone changes in animal models or human use [ 31 , 32 ]. Melsen & Lang, in an animal study, have applied orthodontic forces of 100, 200, and 300 g in three different osseointegrated implant groups.…”
Section: Discussionmentioning
confidence: 99%
“…21 The literature also points to the use of immediate load on these implants, since the orthodontic force, of small magnitude, would cause a very mild increase in stress at the bone-implant interface. 6,26 Marins et al 23 found that endosseous implants submitted to orthodontic forces over a 3-year period not only remained firm, but also sustained a healthy surrounding periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Marins et al 23 conducted peri-implant evaluation of endosseous implants submitted to orthodontic forces and achieved success on 100% of implants submitted to 200cN forces, indicating that they may be safely used for prosthetic rehabilitation after orthodontic finalization. Similarly, Cravero and Ibañez 11 achieved 100% of success on 93 implants used in the maxilla and mandible.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the concept of osseointegration allowed a safe, predictable and durable solution for oral rehabilitation, thus stimulating the development of researches aimed at analyzing the use of dental implants for orthodontic anchorage without compromising the osseointegration (Linkonw, 1969;Majzoub et al, 1999;Saito et al, 2000;Melsen & Lang, 2001;Gotfredsen, Berglundh & Lindhe, 2001a;Gotfredsen, Berglundh & Lindhe, 2001b;Gotfredsen, Berglundh & Lindhe, 2001c;Huang, Shotwell & Wang, 2005;Oyonarte, Pilliar, Deporter & Woodside, 2005;Hsieh et al,2008;Cravero & Ibañez, 2008;Palagi et al, 2010;Ferrari et al, 2015;Podaropoulos et al, 2016;Marins et al, 2016;Rismanchian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed using animal models (Linkonw, 1969;Majzoub et al, 1999;Saito et al, 2000;Melsen & Lang, 2001;Gotfredsen, Berglundh & Lindhe, 2001a;Gotfredsen, Berglundh & Lindhe, 2001b;Gotfredsen, Berglundh & Lindhe, 2001c;Huang, Shotwell & Wang, 2005;Oyonarte, Pilliar, Deporter & Woodside, 2005;Hsieh et al,2008;Ferrari et al, 2015;Podaropoulos et al, 2016;Rismanchian et al, 2017, assembling the histological analysis in addition to the clinical and radiographic analysis, while a few studies in humans (Cravero & Ibañez, 2008;Palagi et al, 2010;Marins et al, 2016) performed clinical, radiographic and Resonance Frequency Analysis (RFA) with the purpose of verifying the bone region around the implants, its stability and possible changes in the implant position.…”
Section: Introductionmentioning
confidence: 99%